(untitled) (Research, Society and Development, 2021)
Known as the science that relates man to his work environments, ergonomics is increasingly necessary for companies and their employees. Since, it allows results and a wide knowledge divided among its domains, characterizing the application of methods governed by the regulatory norm 17. Thus, the objective of this case study is to show the real importance of ergonomics in the office work environment, whose tasks are assigned that impact the physical and psychosocial aspect of employees. In this way, a brief literary review on ergonomics will be presented; areas of ergonomics and ergonomic analysis. Methodology, is a study of quantitative nature. Results obtained: Most of the company’s employees have irregularities in the postural domain, these data represent the number of irregularities by the number of posts. In relation to psychosocial health risk, social support and the quality of leadership is the most common problem among areas of the company sector, with around thirty-four employees affected.